2013
DOI: 10.4236/ojn.2013.31016
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the mental health and sense of coherence (SOC) of new graduate nurses and the effects of SOC on variations in mental health

Abstract: The current research conducted a longitudinal study of new graduate nurses at 3 times-prior to their employment as nurses and 3 months and 1 year afterward. This study yielded 3 findings. 1) The mental health of new graduate nurses significantly worsens 3 months after employment as a nurse and mental health 1 year after employment as a nurse was significantly worse than that before employment. 2) A sense of coherence (SOC) is the ability to cope with stressors, and the 3 components of SOC decreased significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Sense of coherence can affect the mental health of individuals (Takeuchi, 2013;Jiménez et al, 2015). This study reconfirms the strong association between sense of coherence and positive mental health and that sense of coherence can predict positive mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sense of coherence can affect the mental health of individuals (Takeuchi, 2013;Jiménez et al, 2015). This study reconfirms the strong association between sense of coherence and positive mental health and that sense of coherence can predict positive mental health.…”
Section: Discussionmentioning
confidence: 99%
“…SOC reflects a coping capacity and individuals with a strong SOC tend to cope with stress flexibly and effectively (Super et al, 2015). Studies have demonstrated SOC to be an important variable in predicting mental health (Takeuchi, 2013;Krok & Kleszczewska-Albańska, 2019) and the positive relationship between SOC and PMH was also found in mental health professionals (Jiménez et al, 2015). The recent study demonstrates that SOC is an important predictor and modulator of psychopathological symptoms during the COVID-19 pandemic, particularly in those respondents that ruminate about the pandemic (Schäfer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%